Model for Predicting Borderline Mental Disorders of Law Enforcement Officers – Participants of Anti-Terrorist Operation - O. V. Zemlianska; P. V. Makarenko (Law and Safety)
An analysis of the professional tasks of law enforcement officers in the context of an anti-terrorist operation suggests a significant deterioration in their psychological and physical health. Therefore, one of the relevant problems of legal psychology is the development of scientific methods for substantiating and optimizing programs for the psychological provision of the professional activities of law enforcement officers serving in such conditions (professional selection, diagnosis and support of psychological readiness, psychological support, psycho-prophylaxis, correction and rehabilitation). This is necessary to minimize the negative psychosocial consequences in the form of pronounced features of borderline mental disorders and addictive behavior with the formation of concomitant addictions to alcohol and drugs.